Recent advances in metal-organic frameworks for electrochemical sensing applications - Magesh Kumar Muthukumaran; Muthukumar Govindaraj; Sakthivel Kogularasu; Balasubramanian Sriram; Bharathi Kannan Raja; Sea-Fue Wang; Guo-Ping Chang-Chien; Arockia Selvi J (Talanta Open)
Metal-organic frameworks (MOFs) have emerged as promising electrode modifiers in electrochemical sensing owing to their unique structural attributes, such as high surface area, tunable porosity, high catalytic activity, and abundant active sites. These properties make MOF-based systems highly effective for detecting a wide range of analytes, including heavy metals, antibiotics, environmental pollutants, and biomarkers. MOFs offer rapid, cost-effective analysis, yet challenges remain in optimizing their electrochemical properties to fully meet the demands of practical applications, particularly in energy conversion and storage (e.g., supercapacitors, batteries, and water-splitting catalysts) and in the fabrication of high-performance electrochemical sensors. This review critically examines the electrochemical properties of MOF-based materials for detecting various analytes, exploring their current limitations and potential for improvement. Particular focus is given to the design and synthesis strategies that enhance MOFs' structural and electrochemical properties, making them more suitable for real-world applications. Furthermore, this review highlights the challenges associated with MOF stability and conductivity and suggests pathways for overcoming these barriers. Reviewing recent advancements in MOF synthesis and functionality, this article provides a comprehensive overview of how MOFs can be developed as next-generation electrochemical sensing platforms. It also discusses future perspectives, including integrating MOFs into multifunctional sensors and their potential role in wearable and IoT-enabled devices. This review bridges the gap between theoretical research and practical applications, offering valuable insights into the future of MOF-based electrochemical technologies.